Navigating Interoperability, Security, and Scalability: A Narrative Review of IoT Architectures in Smart Cities - Nasihien, Ronny Durrotun; Juwari (Digitus : Journal of Computer Science Applications, 2024)
The rapid advancement of Internet of Things (IoT) technologies has driven the transformation of urban centers into smart cities, yet significant challenges remain in the implementation of interoperable, secure, and scalable IoT architectures. This narrative review aims to explore the primary issues and proposed solutions related to interoperability, cybersecurity, and infrastructure scalability in IoT-based smart city frameworks. Literature was gathered from leading databases including Scopus, Web of Science, and IEEE Xplore, using Boolean search strategies with keywords such as "IoT," "smart cities," "interoperability," "security," and "edge computing." Inclusion criteria focused on peer-reviewed empirical studies published within the past decade. Studies were categorized thematically to identify trends and gaps. The findings show that a lack of interoperability standards remains a major bottleneck, while the growing volume of connected devices amplifies security and scalability concerns. Technical approaches such as Software Defined Networking (SDN), blockchain-based data protection, and edge computing have demonstrated potential in addressing these challenges. However, systemic constraints, including fragmented policies and insufficient data governance, continue to hinder full-scale adoption. The review highlights the importance of adopting a multidimensional framework that incorporates both technological innovations and adaptive policy-making to ensure the successful deployment of IoT in smart city contexts. This study calls for greater cross-sector collaboration, policy reform, and future research into AI-enhanced IoT systems to support inclusive and resilient smart city development.